Pengembangan Aplikasi Evaluasi Pembelajaran Wizer.Me pada Mata Pelajaran IPS di MTs Darussalam Aryojeding - Yulya Basrina; Nila Afryansih; Trina Febriani (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2023)
This study aims to determine and analyze the development, feasibility and practicality of the Development of Evaluation Media Using the Wizer.me Application on Student Learning Outcomes in Social Studies Subjects at MTs Darussalam Aryojeding.The type of research used in this research is research and development (Research and Development). The 4D model includes 4 stages, namely: Define, Design, Development, and Desiminate. The subjects in this study were students of class VIII A and class VIII C who participated in social studies learning at MTs Darusalam Aryojeding 2021/2022, with a total of 82 students. The results of the study found that: 1.) Media development Evaluation includes validation from experts, namely media experts, education experts, linguists and IT experts. So that media validation data is obtained which is then processed with the Interaclass Coefitien Correlation (ICC) formula, assisted by processing using the SPSS version 22 application for Windows, the results are 0.974. if the value is more than 0.5 then it can be concluded that the level of validation is sufficient. 2.) Evaluation media using Wizer.me was declared very feasible after analyzing data processing using Microsoft Excel so that a total score of 1312 was obtained with an average level of 4.0 and a percentage level of 88% with the predicate "Very Eligible". 3.) The evaluation media using Wizer.me was declared practical after processing the research data obtained from the questionnaire, and a practical test was carried out so that a total score of 881 was obtained with an average level of 4.45 and a percentage of 86% in the "Very Practical" category.